News Objectivity of Constitutional Court Decision Number 90/PUU-XXI/2023 on Kompas.com - Budiantari, I Dewa Ayu Diah; Kriyantono, Rachmat (Universitas Brawijaya, 2025)
Objectivity as a key principle of journalism played an important role in news coverage of general elections, particularly in Indonesia. This study analyzed Kompas.com’s coverage of the Constitutional Court’s ruling on the age limit for presidential and vice-presidential candidates, which received significant public attention during the election period. Using J. Westerstahl’s concept of objectivity and a quantitative content analysis method, this study examined 61 news. The findings showed that Kompas.com performed well in terms of factuality, accuracy, transcendence, scope, transparency, causality, suitability image, and congruence language. However, completeness, actuality, suitability language, and congruence image still need improvement to support higher journalistic quality. Therefore, strengthening media governance was required to ensure critical and accountable reporting that protects the integrity of democracy.